Spatial Distribution Analysis of Syrian Immigrant Population Problem in Fatih - Istanbul - Bilen, Omer; Gur, Mehmet; Koc, Ersan; Karahan, Ebru Kamaci (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2020)
Purpose The paper reflects the impacts of the Arab Spring that broke out in Tunisia and Syria and led to the loss of more than 300,000 people. A wave of migration began in 2011, especially from Syria to its neighbouring countries including Turkey and Lebanon. Syrian migratory flows have caused social, economic, and ecological problems in the hosting countries. Turkey is one of the countries most affected by the wave of migration from Syria. Syrian refugees were unequally distributed or dispersed not only in leading metropolitan areas of western Turkey but also in many neighbouring cities in the southeast. The distribution of Syrian refugees in Turkish cities revealed considerable spatial heterogeneity and differences. Design/Methodology/Approach The sample size of the study is 953 and the margin of error of this sample size is +/- 3.17 at a 95% confidence level. Stratified simple random sampling was used. Interviews were Findings Fatih in Istanbul is one of the districts where Syrian immigrants most often settle. As part of the research on social risk mapping for Fatih District, immigrants - especially Syrian immigrants - have been identified as the main cause of problems by residents (the locals), with this group experiencing higher layoffs in terms of economic opportunities. Our analysis found that the main reason why Syrian immigrants are cited as a problem is economic motivation. The rate at which Syrians are declared a problem in the districts of Fatih district is directly proportional to the distribution of the Syrian immigrant population. Research Limitations/Implications Time restriction, unfavourable weather conditions, missing information for socio economic status calculation, reluctance of women to join the survey. Originality/Value This study is the first research which examined spatially, how forced migration has an impact on local residents. Its results that can be useful for social measures towards urban planning and management to reduce the negative effects caused from forced migration population.
Keywords: Forced migration; Syrian refugees; urban security; social integration; spatial analysis; Architecture